Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu dengan Model Student Team Achievement Division (STAD) Di Kelas IV SDN 10 Luhak Nan Duo Kab. Pasaman Barat - Cahyanti, Mega Nur; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research is motivated by the less optimal integrated thematic learning that results in students not understanding the material so that it impacts on learning outcomes. This study aims to describe the Improvement of Integrated Thematic Learning Outcomes Using the Student Teams Achievement Division (STAD) Model in Class IV Students at SDN 10 Luhak Nan Duo, West Pasaman Regency. This type of research is PTK with qualitative and quantitative approaches. Research data in the form of observations and tests. The study was conducted in two cycles. Research subjects are teachers and grade IV students. The results of the study in terms of RPP cycle I 87.5%, cycle II 92%. Teacher activity in cycle I 85.5% (B), cycle II 92.85% category (SB). Cycle I student activities 87.5% (B), Cycle II 92.85% category (SB) Aspects of Cycle I attitude students reflect the main values of mutual cooperation character and do not reflect the main values of religious character, integrity and independence, Cycle II students already reflect the main values of religious characters , mutual cooperation, integrity and independence. It can be concluded in the study that integrated thematic learning using the Student Teams Achievement Division (STAD) model can improve student learning outcomes in primary schools.